A Case of Rheumatoid Arthritis with Bucillamine-Induced Yellow Nail Syndrome Initially Manifesting as Pulmonary Disease - Isozaki, Takeo (Libertas Academica, 2010)
We report a case of a 67-year-old woman with rheumatoid arthritis with yellow nail syndrome (YNS) that was caused by bucillamine. All three signs (yellow fingernails, lymphatic edema, and bronchiectasis) of YNS manifested, with characteristic timing, first with the nails turning yellow after when bronchiectasis was noticed. We reviewed 10 case reports from Japan and compared the periods until the appearance of yellow nails after starting bucillamine treatment, as well as those until lung disease and leg edema appeared.